Study on hydrogen-assisted stress corrosion cracking behavior of 7050 aluminum alloy - Qiang Zhang; Shanshan Shao; Yuhui Huang; Shan-Tung Tu (Journal of Materials Research and Technology)
The effect of hydrogen on the stress corrosion cracking(SCC) susceptibility of 7050 aluminum alloy in 3.5% wt. NaCl solution was investigated by slow strain rate tensile (SSRT) tests with and without hydrogen pre-charging. The experimental results indicated that the stress corrosion cracking (SCC) mechanism of 7050 aluminum alloy is primarily dominated by anodic dissolution, while hydrogen-assisted anodic dissolution during the crack propagation process. The strength and ductility of the aluminum alloy was significantly influenced by hydrogen content. This phenomenon is attributed to hydrogen-induced Mg segregation at grain boundaries, which subsequently facilitates localized anodic dissolution in these regions.